Detoksifikasi Digital dan Pemulihan Rohani: Rekonstruksi Pendidikan Agama Kristen Berbasis Teologi dalam Konteks Kesehatan Mental Siswa - Yohana Fajar Rahayu; Elisa Nimbo Sumual (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2025)
Advanced digital and communication technologies have brought about significant changes in the fields of education and spirituality. However, behind the ease of access to information and communication lies a serious issue: a mental health crisis among students who are addicted to digital devices. This has led to many of them feeling spiritually exhausted and even experiencing emotional burnout. Religious education, which has traditionally focused on cognitive aspects, is deemed insufficiently responsive to the spiritual needs of students. This study aims to reconstruct a Christian religious education approach grounded in theology to facilitate spiritual recovery through digital detoxification practices. The research method used is descriptive qualitative with a literature review approach. It can be concluded that digital detoxification can be an effective spiritual tool in freeing students from the pressures of digital addiction. Therefore, understanding the digital era and the mental health crisis among students must be prioritised. Furthermore, the concepts of theology and spirituality of recovery in Christian education must be able to detoxify digital as a process of Christian spirituality. Thus, this can reconstruct and integrate the Christian religious education curriculum in spiritual recovery.